Jawabanmu

Jawaban paling cerdas!
2013-12-14T17:30:07+07:00
1. f(x) = \frac{ x^{2} -16 }{x - 4} dx

Umpamakan u = {x^{2} -16 dan v = (x - 4)

lalu dengan rumus  \frac{u'.v - v'u}{v^{2} }

=  \frac{(x^{2} -16)'.(x - 4) - (x - 4)'(x^{2} -16)}{(x - 4)^{2} }
=  \frac{ 2x.(x - 4) - (x^{2} -16)}{(x - 4)^{2} }
= \frac{2 x^{2}  - 8x - x^{2} +16}{x^{2} - 8x + 16 }
= \frac{2x^{2}  - 8x - x^{2} +16}{x^{2} - 8x + 16 }
= \frac{x^{2}  - 8x +16}{x^{2} - 8x + 16 }
= 1

2. (4x^{2} + 5x - 3)^{-30} dx
Yang ini diturunin seperti biasa aja

= -30.(4x^{2} + 5x - 3)^{-31} .(4x^{2} + 5x - 3)'
= -30.(4x^{2} + 5x - 3)^{-31} .(8x + 5)
= -30.(8x + 5).(4x^{2} + 5x - 3)^{-31}